Three-dimensional analysis of a cohesive crack coupled with heat flux through the crack. (November 2015) - Jaśkowiec, Jan
Abstract: This paper presents an algorithm for coupling cohesive crack modeling with non-stationary heat flow. Firstly, the nonlinear system of equation, based on global formulations, for such a computational model is derived. The nonlinearity here comes from nonlinear relations in the crack. The relations refer to cohesion forces and to heat flux which both depend of crack opening and additionally are dependent of temperature difference between both sides of the crack. In the paper the discontinuities of displacement field and temperature field are both approximated using XFEM. All the analysis concerning crack surface is performed using local coordinate systems for each integration point. The local coordinate system is two-dimensional for both 2D and 3D analysis. The paper is illustrated with non-stationary thermo-mechanical examples for a domain with propagating crack.